Assessing trait contribution and mapping novel QTL for salinity tolerance using the Bangladeshi rice landrace Capsule - Rahman, M. Akhlasur; Thomson, Michael J.; De Ocampo, Marjorie; Egdane, James A.; Salam, M.A.; Shah-E-Alam, M.; Ismail, Abdelbagi M. (Springer, 2019)
Salinity is one of the most widespread abiotic stresses affecting rice productivity worldwide. The purpose of this study was to establish the relative importance of different traits associated with salinity tolerance in rice and to identify new quantitative trait loci (QTL) conferring tolerance to salinity at seedling stage. A total of 231 F2:3 plants derived from a cross between a sensitive variety BRRI dhan29 (BR29 hereafter) and Capsule, a salt tolerant Bangladeshi indica landrace, were evaluated under salt stress in a phytotron Out of the 231 F2 plants, 47 highly tolerant and 47 most sensitive lines were selected, representing the two extreme tails of the phenotypic distribution. These 94 plants were genotyped for 105 simple sequence repeat (SSR) and insertion/deletion (InDel) markers. A genetic linkage map spanning approximately 1442.9 cM of the 12 linkage groups with an average marker distance of 13.7 cM was constructed. QTL were identified on the long arm of chromosome 1 for Na+ concentration, K+ concentration, Na+-K+ ratio and survival; chromosome 3 for Na+ concentration, survival and overall phenotypic evaluation using the Standard Evaluation system (SES); and chromosome 5 for SES. A total of 6 pairwise epistatic interactions were also detected between QTL-linked and QTL-unlinked regions. Graphical genotyping indicated an association between the phenotypes of the extreme families and their QTL genotypes. Path coefficient analysis revealed that Na+ concentration, survival, Na+-K+ ratio and the overall phenotypic performance (SES score) are the major traits associated with salinity tolerance of Capsule Capsule provides an alternative source of salinity tolerance aside from Pokkali and Nona Bokra, the two Indian salt tolerant landraces traditionally used for breeding salt tolerant rice varieties. Pyramiding the new QTL identified in this study with previously discovered loci, such as Saltol, will facilitate breeding varieties that are highly tolerant of salt stress.